Biosorption of Cu(II) and Zn(II) by intact and pre-treated biomass of Oscillatoria planctonica. (23rd June 2009) - Peng, Hui; Liu, Yunguo; Zeng, Guangming; Li, Xin; , Wei Zhang
The biosorption of copper(II) and zinc(II) from aqueous solution by intact and pre-treated biomass of Oscillatoria planctonica was studied. The biosorption was pH dependent and the adsorption capacity decreased with the biosorbent to solution ratio increasing. The maximum removal ratios were 84.84% and 68.22% respectively in pre-treated biomass. The biosorption followed both the Langmuir and Freundlich isotherm model and the adsorption equilibrium was reached in about 1 h. The adsorbed Cu(II) and Zn(II) could be desorbed effectively by 0.1 M nitric acid. The experimental results indicated that Oscillatoria planctonica was effective in removing Cu(II) and Zn(II) from wastewater.